Analysis of Students’ Mathematical Comprehension Ability Against Mathematics Teaching Materials with Constructivism Through Mobile Learning System - Wahyuni, Yusri; Alyusfitri, Rieke (IJRDO- Journal of Educational Research, 2017)
This objective of this study was to analyze the achievement of each indicator of students’ mathematical comprehension of mathematics teaching materials with constructivism approach through mobile learning system. This research was qualitative descriptive research that described the ability of students’ mathematical comprehension analysis. The subject of the research was the students of Bung Hatta University Mathematics Education Major which took the academic year of 2016/2017 which consisted of 25 students. Data collection methods used students’ mathematical comprehension skills after using instructional materials with constructivism approach through mobile learning system. Based on the results of the research it can be concluded that the achievement of the mathematical comprehension ability to the indicator of classifying objects according to certain properties shown by the questions 2 and 5 are 55% and 67%. The indicator of the students’ ability to use, utilize, and select a particular procedure or operation which is indicated by question 1 is 87.5%. And the indicator of ability to apply concept or algorithm in problem-solving shown on questions 3 and 4 are 92% and 90%.